Antimicrobial activity of Epsilon-Poly-l-lysine against phytopathogenic bacteria - Bárbara Rodrigues; Tâmara P. Morais; Paulo A. Zaini; Cássio S. Campos; Hebréia O. Almeida-Souza; Abhaya M. Dandekar; Rafael Nascimento; Luiz R. Goulart (Scientific Reports, 2020)
Abstract Antimicrobial peptides (AMPs) are components of immune defense in many organisms, including plants. They combat pathogens due to their antiviral, antifungal and antibacterial properties, and are considered potential therapeutic agents. An example of AMP is Epsilon-Poly-l-lysine (EPL), a polypeptide formed by ~ 25 lysine residues with known antimicrobial activity against several human microbial pathogens. EPL presents some advantages such as good water solubility, thermal stability, biodegradability, and low toxicity, being a candidate for the control of phytopathogens. Our aim was to evaluate the antimicrobial activity of EPL against four phytobacterial species spanning different classes within the Gram-negative phylum Proteobacteria: Agrobacterium tumefaciens (syn. Rhizobium radiobacter), Ralstonia solanacearum, Xanthomonas citri subsp. citri (X. citri), and Xanthomonas euvesicatoria. The minimum inhibitory concentration (MIC) of the peptide ranged from 80 μg/ml for X. citri to 600 μg/ml for R. solanacearum and X. euvesicatoria. Two hours of MIC exposure led to pathogen death due to cell lysis and was enough for pathogen clearance. The protective and curative effects of EPL were demonstrated on tomato plants inoculated with X. euvesicatoria. Plants showed less disease severity when sprayed with EPL solution, making it a promising natural product for the control of plant diseases caused by diverse Proteobacteria.